PERSEPSI MASYARAKAT TERHADAP ETIKA PERGAULAN MAHASISWA KOST DI RT 03 KELURAHAN BANSIR DARAT KECAMATAN PONTIANAK TENGGARA - Febriyani, Devi; Sulistyarini, Sulistyarini; Rustiyarso, Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThesis title "Societys? Perception on the Social Ethics of the College Students Live in Dormitory at RT 03 Kelutahan Bansir Darat Kecamatan Pontianak Tenggara". The main problem in this research is how is societys? perception towards social ethics of the college students who live at dormitory. This research uses qualitative approach with descriptive method. Technique data collection used are observation techniques, interviews, and documentation study. The results showed that: (1) Societys? appraisement towards social ethics of the college students showed that students who are sociable proven fairly with greeting and smile, interaction with society has not been good yet because interaction occurs only when there is needs (2) Forms of violation have done by the college students are coming home over time which it has to be not later than 11 pm and guest of the opposite sex visiting hours which it has to be not later than 10 pm (3) The control towards college students showed that the preventive and repressive controls done by society leader and the dorm owner towards college students is quite good because the prevention through rules and repressive reprimand in the form of warning, punishment in the form of expelling and advice in the form of calling students who violated the rules have been conducted.Keywords: Perception, Social Ethics, College students live in dormitory